Børnelitteratur i udbrud. Transmediale bevægelser i nutidig børnelitteratur - Mygind, Sarah (Passage - Tidsskrift for litteratur og kritik, 2016)
“Children’s Literature Erupting. Transmedia Movements in Contemporary Children’s Literature” The rise of large transmedia storytelling systems such as Harry Potter, The Hunger Games and Game of Thrones suggests that transmedia storytelling is the most important narrative mode of our time. However, transmedia storytelling also exists and works on other scales. This article focuses on a growing transmedia storytelling practice that has remained underexposed as such in the field of research due to the dominance of the large transmedia franchises. This practice is indeed related to transmedia storytelling but it also challenges existing theories. With a number of different media publications all named The Numberlys produced by Moonbot Stu- dios as its point of departure, the article explores the underlying structures, relations and mechanisms in and between these publications in order to elucidate aesthetic consequences of the transmedial ‘eruptions’ in contemporary media entertainment products for children.